Socioeconomic, demographic, and clinical profile of COVID patients in north coastal districts of Andhra Pradesh - Siva Prasad Reddy Basava,; Aruna Rani Behera,; Sangeeta Panigrahy,; Pradeep Vegi,; Samatha P,; Balachandrasekhar P,; Sai Saileshkumar Goothy, (Asian Journal of Medical Sciences, 2022)
Background: The unprecedented outbreak of a contagious respiratory disease caused by a novel coronavirus has led to a pandemic since December 2019, claiming millions of lives. Aims and Objectives: The present study was undertaken to estimate the various risk factors associated with COVID, to study the common presenting symptoms and prognosis, and to estimate the degree of association between computed tomography (CT) value in reverse transcription polymerase chain reaction (RT-PCR) with mode of disease transmission in north coastal districts of Andhra Pradesh. Materials and Methods: This was a cross-sectional study comprising of 1462 COVID-positive individuals. It is based on structured questionnaire on demographic, socioeconomic and symptoms, and correlation of clinical pattern with CT value in RT-PCR and further prognosis. Results: Diabetes (6.7%), hypertension (7.5%), and bronchial asthma (8.6%) are the main comorbid conditions. Middle (44.6%) and low socioeconomic status (47.3%) are more susceptible. Male gender (63.5%) is more affected, especially 16–30 years age group (32.4%). Vaccination offers considerable protection from infection. Contact (59.4%) with known case and travel (31%) are main factors that determine disease transmission. Blood group may not play a role in COVID susceptibility. Health care workers (22.9%) and students (16.2%) are mostly affected. Conclusion: Bronchial asthma, hypertension, and diabetes mellitus are the predominant risk factors associated with COVID. Transmission of the disease is more by virtue of contact with the infected person than by travel.